2013
DOI: 10.3844/jssp.2013.1.10
|View full text |Cite
|
Sign up to set email alerts
|

Change Over Time in the Human Immunodeficiency Virus Risk Perceptions of Youth

Abstract: Although the vulnerability of young people to HIV/AIDS continues to be a serious concern in South Africa, no research has used a representative sample of South African youth to examine whether individual Human Immunodeficiency Virus (HIV) risk perceptions change over time and, if they do, what factors are associated with change. Using data from the Cape Area Panel Study, a multi-racial, longitudinal study of youth and their households, this study examined whether youth change their HIV risk perceptions over a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…As it is not plausible that decreased risk perception causes condom use, this supports the hypothesis that there is a circular feedback between risk perception and condom use, so those who implemented the protective behaviour (condom use) adjust their risk perception downward (hypothesis 2). As opposed to a previous study in South Africa that similarly concluded that increased risk perception leads to condom use [32], influences of sexual debut and HIV infection were eliminated by restricting analyses to those HIV-negative and sexually active, and changes in other socio-demographic and behavioural factors that may confound associations between risk perception and condom use were controlled for.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As it is not plausible that decreased risk perception causes condom use, this supports the hypothesis that there is a circular feedback between risk perception and condom use, so those who implemented the protective behaviour (condom use) adjust their risk perception downward (hypothesis 2). As opposed to a previous study in South Africa that similarly concluded that increased risk perception leads to condom use [32], influences of sexual debut and HIV infection were eliminated by restricting analyses to those HIV-negative and sexually active, and changes in other socio-demographic and behavioural factors that may confound associations between risk perception and condom use were controlled for.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, for HIV testing, reverse causality is plausible, so HIV testing and counselling could cause a change in risk perception (not risk perception causing testing). In another study of the same population, males who started perceiving a risk between two surveys were more likely to report condom use during the second survey [32]. For condoms, risk perception is likely to have a stronger effect than for HIV testing and reverse causality is less likely given that starting to use condoms is implausible to cause increasing risk perception (although an increase in condom use could decrease risk perception).…”
Section: Introductionmentioning
confidence: 98%
“…As it is not plausible that decreased risk perception causes condom use, this supports the hypothesis that there is a circular feedback between risk perception and condom use, so those who implemented the protective behaviour (condom use) adjust their risk perception downward (hypothesis 2). As opposed to a previous study in South Africa that similarly concluded that increased risk perception leads to condom use (32), influences of sexual debut and HIV infection were eliminated by restricting analyses to those HIV-negative and sexually active, and changes in other sociodemographic and behavioural factors that may confound associations between risk perception and condom use were controlled for.…”
Section: Discussionmentioning
confidence: 99%
“…In another study of the same population, males who started perceiving a risk between two surveys were more likely to report condom use during the second survey. (32) For condoms, risk perception is likely to have a stronger effect than for HIV testing and reverse causality is less likely given that starting to use condoms is implausible to cause increasing risk perception (although an increase in condom use could decrease risk perception). However, the study failed to account for condom use at baseline and included those who started to become sexually active between surveys, which the study itself found to be associated with developing risk perception.…”
Section: Introductionmentioning
confidence: 99%